Pengaruh Kompres Aloe Vera Terhadap Penurunan Suhu Tubuh Pada Anak Tifoid Di Ruang Cendana RSUD Kardinah Tegal - Pradana, Dicky Yudhistira; Yunida Triana, Noor (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2025)
Acute systemic infectious disease caused by the microorganism salmonella enterica serotype typhi known as Salmonella typhi (S. typhi) is called typhoid, the symptoms that arise include an increase in body temperature> 37.5oC or called fever. Nursing care that can be done to reduce body temperature in children with fever, namely using non-pharmacological therapy by means of aloe vera compresses. The purpose of this study was to compile Nursing Care for Hyperthermia in Typhoid Children in the Upper Cendana Room at Kardinah Hospital Tegal. The purpose of this study was to determine the effect of aloe vera compress on reducing body temperature in typhoid children in the Cendana Room of Kardinah Tegal Hospital. The research design was a case study conducted for 3 days with a focus on the intervention of aloe vera compresses on typhoid children in the Cendana Room of Kardinah Hospital Tegal. The results of this study were obtained in An. M after doing aloe vera compress for 3 days experienced a decrease in fever, seen on the first day the child had a fever with a body temperature of 38oC and decreased on the second day to 36.8oC and on the third day 36.2oC, the conclusion is that aloe vera compresses can reduce fever in typhoid children. Suggestions for further researchers are expected to examine other non-pharmacological therapies to reduce the body temperature of typhoid children.